Reductions in Positive Clostridioides difficile Events Reportable to NHSN With Adoption of Reflex EIA Testing in 13 Atlanta Hospitals. (October 2020) - Goodenough, Dana; Sefton, Samantha; Smith, Elizabeth; Kraft, Colleen; Varkey, Jay; Fridkin, Scott
Abstract : Background: US hospitals are required to report C. difficile infections (CDIs) to the NHSN as a performance measure tied to payment penalties for poor scores. Currently, only the charted CDI test results performed last in reflex testing scenarios are reported to the NHSN (CDI events). We describe the reduction in NHSN CDI events from the addition of a reflex toxin enzyme immunoassay (EIA) after a positive nucleic acid amplification test (NAAT) in teaching and nonteaching hospitals, and we estimate the impact on standardized infection ratios (SIR). Methods: Reporting of all CDI test results, by test method, occurred during April 2018–July 2019 to the Georgia Emerging Infections program (funded by the Centers for Disease Control and Prevention), which conducts active population-based surveillance in an 8-county Atlanta area (population, 4 million). Among facilities starting reflex EIA testing, results were aggregated by test method during months of reflex testing to calculate facility-specific reduction in NHSN CDI events (% reduction; 1-[no. EIA+/no. NAAT+]). Differences in percent reduction between facilities by characteristic were compared using the Kruskal-Wallis test. We simulated expected changes in the SIR for a range of reductions, assuming equal effect on both community-onset (CO) and hospital-onset (HO) tests. Each facility's historical NHSN CDI events prior to reflex testing were used to estimate changes to facility-specific SIRs by reducing values by the corresponding facility's percent reduction. Results: Overall, 13 acute-care hospitals (bed size, 52–633; ICU bed size, 6–105) started reflex testing during the study period (mean, 7 months, 15, 800 admissions, 66, 400 patient days), resulting in 550 +NAAT tests reflexing to 180 +EIA tests (pooled mean 58% reduction). Percent reduction varied (mean, 67%; range, 42%–81%) but did not differ between larger (≥217 beds) and smaller hospitals (61 vs 50% reduction; P > .05) or by outsourced versus inhouse testing (65% vs 54% reduction; P > .05). Simulations identified a threshold reduction at which point effect on HO counteract the effects on CO events enough to reduce the SIR; thresholds for nonteaching and teaching were 26% and 32% reduction, respectively (Fig. 1). The estimated reductions in facility-specific SIRs using measured percent reductions on historic NHSN CDI events closely paralleled the simulation, and the mean estimated change in SIR was −46% (range, −12% to −71%) (Fig. 1). Conclusions: Although the magnitude of the effect varied, all 13 facilities experienced dramatic reductions in CDI events reportable to NHSN due to reflex testing; applying these reductions to historical NHSN data illustrates anticipated reductions in their facility-specific SIRs due to this testing change. Funding: None Disclosures: Scott Fridkin, consulting fee, vaccine industry (various) (spouse)